DINASTI BANI UMAYYAH DI SURIAH - Jabir, Muh. (Hunafa: Jurnal Studia Islamika, 2007)
When the Prophet Muhammad died in 632 AH., the Islamic territory spread out not only in Madinah, but also Â throughout the Arab peninsula. After Muawiyah bin Abi Sufyan defeated Ali bin Abi Thalib, the fourth caliph of Islam, in the battle of Shiffin, he founded a dynasty called after his name, the Muawwid Dynasty. It was in the epoch of Muawiyah that the style of governance, which in the period of al-Khulaf Â al-Rasyidun Â was still democratic, became a monarchic system of governance. From the epoch of Muawiyahâs rule in Damascus onwards, the Dynasty Â was ruled based on his offspring. Therefore, it was Muawiyah the first political leader of Islam who implemented the monarchic government system throughout the history of Political Islam.Â Kata Kunci: Dinasti Umayyah, sistem pemerintahan demokrasi, sistem pemerintahan monarki